Actual Time Departure Coordination Application Between Tower Units and FIC Units Based on Website - Yuliadi Mubarok, Achmad; Rochmawati, Laila; Akbar Awal Rozaq, Hasri; Putra, Iwansyah (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Reporting from movement message data in the ATS RO Logbook Operational Airnav Sentani. in one of day, Sentani serves more than 100 flights with an average breakdown of 69 departure movements and 72 arrival movements with a total of 141 movements every single day so that with sending departure messages that are still manual, delays and irregularities often occur. suitability. Because of this, the authors developed a website as a coordination tool so that recording data departures was easier and faster. The purpose of writing this final project is to answer the formulation of the problem, namely to design a Website-based Actual Time Departure Coordination Application between the TOWER Unit and FIC at Perum LPPNPI Sentani Branch.The research method used in making this website is Research and Development with the waterfall method. This method is carried out with a systematic approach, starting from the system requirements stage, then moving on to the Requirements Analysis, Design, Implementation, Integration and System testing stages, and maintenance with testing techniques. used is black box testing. The results of this study are expected to assist ATS personnel at the FIC Unit at Airnav Sentani in sending Departure Messages in order to improve flight service and safety